Does actual overweight or perception of overweight elevate suicide risk in bullied vs. non-bullied students? - Ashley Kalle; Yunmi Chungs; Wonksuk Yoo (Journal of the Georgia Public Health Association, 2016)
Background: For individuals in Georgia aged 10-14 and 15-24, suicide is the third leading cause of death. Those who are overweight are often bullied by their peers, and being bullying can lead to higher risks of suicidality. There is, however, mixed evidence about the relationship between high weight and suicide. Weight perception may be a stronger predictor of suicide than actual weight. The aim of the present study was to examine, in a national sample of high school students, the interaction between weight and bullying on suicide outcomes. Methods: A secondary data analysis was performed with data from the 2015 Youth Behavior Risk Surveillance Survey (YRBSS), a cross-sectional survey of high school students nationwide conducted by the Centers for Disease Control and Prevention. The predictor variables analyzed were actual overweight, overweight perception, and bullying. The outcome variables were suicide ideation, suicide planning, and suicide attempts. Results: For non-bullied students, perception of overweight was a predictor of suicide risk. Whether actual overweight or perception of overweight increases suicide risk in bullied students depended on the type of bullying. For being bullied at school only and being bullied at school and online, overweight perception increased suicide risks. For being bullied online, actual overweight increased suicide risks. Conclusions: Interventions that target bullied students and decrease body dissatisfaction may lower suicide attempts.